PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PESERTA BPJS KESEHATAN DI BADAN LAYANAN UMUM DAERAH (BLUD) RUMAH SAKIT UMUM CUT NYAK DHIEN MEULABOH - Rinda Pramadia; Muliza (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2019)
This study aims to determine the Effect of Service Quality on Satisfaction of BPJS Health Participants at BLUD Cut Nyak Dhien Meulaboh Regional General Hospital using questionnaires as research instruments. The number of samples in this study were 60 respondents, with a purposive sampling technique. Data analysis technique used is multiple linear regression using the help of IBM SPSS 23.0 software. The results of this study show that the variable of reliability andresponsiveness partially have a significant effect on the participants’ satisfaction with a significance value of the reliability variable of 0.039 <0.05 and the responsiveness variable of 0.00 <0.05. Meanwhile, the variable of guarantee, physical evidence and empathy do not significantly influence the satisfaction of the participants of Healthcare BPJS in the BLUD of Cut Nyak Dhien Regional General Hospital of Meulaboh. On the other hand, the simultaneous testing (F-test) shows that all variables in this study significantly affect the participants’ satisfaction with a significance value of 0.000 <0.005. In addition, the coefficient of determination obtains the R squared value of 0.760 which means that the independent variables, reliability, responsiveness, empathy, physical evidence and guarantee, affect the satisfaction of Healthcare BPJS participants in the BLUD of Cut Nyak Dhien Regional General Hospital of Meulaboh by 76%. The remaining 34% is affected by other variables that are not included in this study.